2011
DOI: 10.1128/aac.01487-10
|View full text |Cite
|
Sign up to set email alerts
|

Joint Population Pharmacokinetic Analysis of Zidovudine, Lamivudine, and Their Active Intracellular Metabolites in HIV Patients

Abstract: The population pharmacokinetic parameters of zidovudine (AZT), lamivudine (3TC), and their active intracellular metabolites in 75 naïve HIV-infected patients receiving an oral combination of AZT and 3TC twice daily as part of their multitherapy treatment in the COPHAR2-ANRS 111 trial are described. Four blood samples per patient were taken after 2 weeks of treatment to measure drug concentrations at steady state. Plasma AZT and 3TC concentrations were measured in 73 patients, and among those, 62 patients had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
(54 reference statements)
3
13
1
Order By: Relevance
“…Bazzoli et al (30) found an effect of gender on CL/F, but no significant differences between administration route and gender were found in the present study.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Bazzoli et al (30) found an effect of gender on CL/F, but no significant differences between administration route and gender were found in the present study.…”
Section: Discussioncontrasting
confidence: 40%
“…The stability of the model was improved when the value was fixed to 2.86 h Ϫ1 . This value was reported by Panhard et al (28) and used in another study (30).…”
Section: Zdv Population Pharmacokineticsmentioning
confidence: 67%
See 1 more Smart Citation
“…These data indicate that lamivudine or emtricitabine have a long enough intracellular half-life for reduction of viral resistance to NNRTI (1). Previously reported data for nevirapine in the prevention to mother-to-child transmission support these findings (2,3,13).…”
supporting
confidence: 78%
“…One study of ZDV-3TC-indinavir among 29 men and 4 women demonstrated approximately 2-fold higher ZDV-TP and 1.4-fold higher 3TC-TP levels in women (4). Other studies have shown similar results for ZDV-phosphates (10,38), but still others have shown opposite results for ZDV-phosphates (8). Given possible differences in NRTI response, there is an urgent need for additional comparisons of NRTI cellular pharmacology by sex.…”
mentioning
confidence: 79%